Possible ways of pharmacological correction of ischemic liver damages using agonist of peripheral imidazoline receptors c7070 - Dovgan, A. P.; Povetkin, S. V.; Batishcheva, G. A.; Dolzhikov, A. A.; Pokrovsky, M. V.; Urozhevskaya, Z. S. (I.P. Pavlov Russian Medical Biological Herald, 2018)
A comorbid condition both in diabetes mellitus and in metabolic syndrome is fatty dystrophy of the liver that further progresses to hepatic necrosis. In the article variants of pharmacological correction of ischemia-reperfusion of the liver with agonists of imidazoline receptor are proposed. Materials and Methods. The experiment was conducted on 70 rats of both sexes divided into 7 groups (n=10): intact group; pseudo-operated animals (incision of the abdominal wall without ligation of hepatic vessels); animals subject to ischemia/reperfusion without drug correction; animals subject to ischemia/reperfusion of the liver + metformin (50 mg/kg); animals subject to ischemia/reperfusion of the liver + moxonidine (1 μg/kg); animals subject to ischemia/reperfusion of the liver+С7070 (10 mg/kg). For evaluation coefficients were used calculated from the level of hepatic transaminases: alaninaminotranspherase (ALT), aspartataminotranspheras (AST), – and also from morphometric ratios of the areas of necrosis and deep ischemia of the liver on the basis of histological examination. Results. Agonist of peripheral imidazoline receptors C7070 reduces ischemic-reperfusion damages to the liver to a significantly larger extent than moxonidine and metformin. Hepatoprotective effect of C7070 was removed by preliminary introduction of peripheral imidazoline receptor blocker. ALT/AST coefficients for C7070, moxonidine and metformin were 72.8/62.13; 44.99/34.20 and 36.88/21.02, respectively. Coefficients of morphological hepatoprotective activity of the drugs were: С7070 – 82.61, moxonidine – 72.33, metformin – 38.96. Conclusion. Agonists of imidazoline receptors reliably and significantly reduce functional and morphological manifestations of ischemia/reperfusion of the liver.